A Study of New Results for the Existence in Vector Spaces of Solutions of Generalized Variations Such As Inequalities for Multi-Functions: Solutions for generalized nonlinear non-linear vector inequalities in local, convex, topological vector spaces (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article examines a class of widespread non-linear vector inequalities and nearly variable characters with maps in Hausdorff's topological vector space areas which include popular, non-linear, mixed variable inequalities, widespread, mixed, near-variable inequalities, etc. We obtain solutions for generalized, nonlinear non-linear vector inequalities in local, convex, topological vector spaces, using a fixed-point theorem.